Analisis Yuridis Pertanggungjawaban Pidana terhadap Pelaku Penyalahgunaan Data Pribadi dalam Transaksi Elektronik di Indonesia - M. Resko; Siti Rahmah; Bambang Sasmita Adi Putra (Journal of Innovative and Creativity (Joecy), 2026)
The rapid growth of digital technology has increased the risk of personal data misuse in electronic transactions, creating significant legal challenges in Indonesia. This study aims to analyze criminal liability for perpetrators of personal data misuse, examine the application of the lex specialis derogat legi generali principle between the Personal Data Protection Law and the Electronic Information and Transactions Law, and identify obstacles to law enforcement. This research employed a normative juridical method using statutory, conceptual, and case approaches. Legal materials consisted of primary, secondary, and tertiary legal sources analyzed qualitatively through a prescriptive approach. The findings indicate that criminal liability may be imposed on both individuals and corporations that unlawfully obtain, disclose, or misuse personal data. Although the Personal Data Protection Law provides a more specific legal framework, practical implementation still encounters regulatory overlap, limited institutional capacity, digital evidence challenges, and inadequate cyber law expertise among law enforcement officers. Therefore, harmonization of regulations, institutional strengthening, and enhancement of digital forensic capabilities are essential to ensure effective legal protection and legal certainty.